Fintech adoption in Vietnam: The moderating role of explainable artificial intelligence - Nguyen, Van Tho; Le, Trung Nhan; Van Ban, Van Ban (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
This study examines the importance of Explainable Artificial Intelligence (XAI) in promoting the acceptance of financial technology (Fintech) in Vietnam. It emphasizes that XAI is not only a technical factor but also a crucial element in building trust and facilitating Fintech adoption in the country. In the context of the rapidly growing Fintech sector, the transparency and interpretability of AI algorithms are essential for fostering consumer trust. In Vietnam, the development of the Internet and technology has been strong in recent years, however, some consumers are still hesitant to use Fintech applications for a number of reasons, among which security is a factor that users are concerned about. Users are more inclined to accept financial technologies when they understand how AI operates and its decisions. Clear explanations enhance users' confidence in utilizing Fintech services, improving their experience and satisfaction. The research indicates that providing transparent information about the functioning of AI can increase the likelihood of Fintech acceptance, particularly in areas such as online lending and investment management. The findings reveal that factors such as Financial Literacy, Financial Satisfaction, Usefulness, and Brand Image have a positive impact on Fintech adoption. In contrast, Security and Ease of Use do not significantly influence Fintech acceptance. This research result helps businesses to refer to and have a strategy to integrate XAI into Fintech applications to attract customers to accept Fintech to optimize profits.